2018
DOI: 10.1097/md.0000000000012911
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perioperative allogeneic blood transfusion on prognosis of hepatocellular carcinoma after radical hepatectomy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Secondly, perioperative blood transfusions were independently associated with survival and cancer recurrence after surgical resection ( 36 ). A meta-analysis found that allogeneic blood transfusions were associated with poor clinical prognoses in patients with HCC who underwent radical hepatectomy ( 37 ). The association between major resection and blood loss as well as RFS of HCC patients has been examined: the more complicated hepatectomy is, the more likely patients are to suffer from intraoperative blood loss, leading to shorter time to recurrence ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, perioperative blood transfusions were independently associated with survival and cancer recurrence after surgical resection ( 36 ). A meta-analysis found that allogeneic blood transfusions were associated with poor clinical prognoses in patients with HCC who underwent radical hepatectomy ( 37 ). The association between major resection and blood loss as well as RFS of HCC patients has been examined: the more complicated hepatectomy is, the more likely patients are to suffer from intraoperative blood loss, leading to shorter time to recurrence ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The median duration of the PM in the present study was less than 20 minutes. Conversely, blood loss during hepatectomy and subsequent perioperative blood transfusion has been associated with poor overall and disease-free survival in hepatocellular carcinoma patients 35,40 . Therefore, not only does a shorter PM not increase the recurrence rate but it may even reduce it by preventing excessive blood loss and need for a blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Other than these factors, several clinical factors have also been suggested in association with cancer prognosis [18,19]. Among these, blood transfusion using allogeneic pRBC units has been extensively examined in various types of cancer, and these studies have suggested a deleterious effect on prognosis [3][4][5][6][7]. In addition to the combined impact of surgery and anesthesia-induced immunosuppression, administration of blood products can further aggravate the immunosuppressive status of cancer patients, resulting in transfusion-related immune modulation (TRIM).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, curative surgery for malignancy is always associated with the risk for massive bleeding; therefore, the probability of blood transfusion may also increase. However, the results of several meta-analyses have consistently indicated the existence of a negative association between perioperative blood transfusion (PBT) and oncologic outcomes, including tumor recurrence and survival, in surgically treated patients with various malignancies, including stomach, lung, liver, and colorectal cancer [3][4][5][6][7]. Although the mechanism underlying this unfavorable association is not fully understood, it is hypothesized that immune modulation and inflammatory responses caused by PBT adversely affect oncologic outcomes after radical surgery for cancer [1,2,8].…”
Section: Introductionmentioning
confidence: 99%